1989
DOI: 10.1029/wr025i007p01583
|View full text |Cite
|
Sign up to set email alerts
|

Field scale transport of bromide in an unsaturated soil: 2. Dispersion modeling

Abstract: The solute concentrations measured in the field experiment of G. L. Butters et al. (this issue) are used to compare two models of vadose zone solute transport: the deterministic one-dimensional convection-dispersion model, which represents solute transport far from the source of solute entry, and the stochastic-convective lognormal transfer function model, which represents solute transport near the source. The stochastic-convective model provided an excellent representation of the spreading of the solute pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 25 publications
2
71
2
2
Order By: Relevance
“…Para a condição de campo ou em escalas de aquífero, está bem estabelecido que a dispersividade (λ) aumenta com o aumento do percurso (Butters & Jury, 1989;Gelhar et al, 1992;Basha & El-Habel, 1993). No entanto, resultados de estudos com colunas em laboratório em que foi avaliado o efeito do comprimento da coluna sobre a dispersividade são inconsistentes.…”
Section: Introductionunclassified
“…Para a condição de campo ou em escalas de aquífero, está bem estabelecido que a dispersividade (λ) aumenta com o aumento do percurso (Butters & Jury, 1989;Gelhar et al, 1992;Basha & El-Habel, 1993). No entanto, resultados de estudos com colunas em laboratório em que foi avaliado o efeito do comprimento da coluna sobre a dispersividade são inconsistentes.…”
Section: Introductionunclassified
“…These cores were carefully driven horizontally into the shaved sidewall of the pits to obtain approximately undisturbed soil samples. Butters [1987] measured the particle size distribution in the field from samples obtained by soil coring. To supplement his results, particle size analyses were performed using the pipette method [Day, 1965] for all applications were 57.6, 39.3, and 2.7 mol m -3 for Ca(NO3)2, KC1, and H3BO 3, respectively.…”
Section: Field Descriptionmentioning
confidence: 99%
“…Without understanding the mechanisms and extent of lateral dispersion it is not possible to predict even roughly the downward displacement of solutes injected at the surface [Ellsworth et al, 1991;Flahler et al, 1996]. It has been experimentally demonstrated that stratifications in soil affect solute dispersion considerably, often causing an abrupt decrease of the longitudinal dispersion and an increase of lateral mixing [Butters and Jury, 1989; Roth et al,…”
Section: Introductionmentioning
confidence: 99%